PSYCHOLOGICAL CONTRACT VIOLATION AND EFFORT WITHHOLDING: MEDIATING ROLE OF WORK CONDITIONS AMONG SMEs IN LAGOS - Akinbode, Gabriel Aunde (African Journal of Social and Behavioural Sciences, 2025)
This study examined the influence of psychological contract violations on employee effort withholding behaviours while considering the mediating roles of conditions of work effectiveness among selected workers of SMEs operating in the Lagos metropolis, Nigeria. A psychological contract breach can result in changes in employee behaviour, commitment and obligation toward the organization. Based on the social exchange theory of George Homan, this study employs a mixed design of ex-post-facto and cross-sectional survey techniques to collect data from 426 employees across some selected SMEs sampled for the study. The findings revealed a negative relationship between psychological contract violation variables and effort-withholding behaviours. It was established that because the psychological contract is grossly unmet (i.e. very low), workers engaged themselves in a variety of effort-withholding behaviours. Specifically, aptly mediated by the condition of work effectiveness, work environment, compensation and job characteristics contract violations accounted for 42.4%, 51.8% and 13.2% of the observed variance in work effort withholding behaviours among the sampled workers. It was also established that there were significant gender and age differences in effort withholding behaviours: effort withholding was higher among young adults, middle-aged and older females than their male counterparts. The findings in this present study underscored the much-taunted, perceived vibrancy and resilience of middle-aged female employees in many organizations in Nigeria in recent times.